A Black Raspberry-Rich Diet Protects From Dextran Sulfate Sodium-Induced Intestinal Inflammation and Host Metabolic Perturbation in Association With Increased Aryl Hydrocarbon Receptor Ligands in the Gut Microbiota of Mice - Tu, Pengcheng; Chi, Liang; Bian, Xiaoming; Gao, Bei; Ru, Hongyu; Lu, Kun (Frontiers in Nutrition, 2022)
Dietary modulation of the gut microbiota recently received considerable attention, and ligand activation of aryl hydrocarbon receptor (AHR) plays a pivotal role in intestinal immunity. Importantly, black raspberry (BRB, Rubus occidentalis) is associated with a variety of beneficial health effects. We aim to investigate effects of a BRB-rich diet on dextran sulfate sodium (DSS)-induced intestinal inflammation and to determine whether its consequent anti-inflammatory effects are relevant to modulation of the gut microbiota, especially its production of AHR ligands. A mouse model of DSS-induced intestinal inflammation was used in the present study. C57BL/6J mice were fed either AIN-76A or BRB diet. Composition and functions of the gut microbiota were assessed by 16S rRNA sequencing and comparison metagenome analysis. Metabolic profiles of host and the gut microbiome were assessed by serum and fecal metabolomic profiling and identification. BRB diet was found to ameliorate DSS-induced intestinal inflammation and host metabolic dysbiosis. BRB diet also restored diversity and composition in the gut microbiota. BRB diet promoted AHR ligand production by the gut microbiota, as revealed by increased levels of fecal AHR activity in addition to increased levels of two known AHR ligands, hemin and biliverdin. Accordingly, enrichment of bacterial genes and pathways responsible for production of hemin and biliverdin were found, specific gut bacteria that are highly correlated with abundances of hemin and biliverdin were also identified. BRB dietary intervention ameliorated intestinal inflammation in mice in association with promotion of AHR ligand production by the gut microbiota.